Foraging Behavior and Energetics of Albatrosses in Contrasting Breeding Environments - Antolos, Michelle; Shaffer, Scott A.; Weimerskirch, Henri; Tremblay, Yann; Costa, Daniel P. (Frontiers in Marine Science, 2017)
Animals can maximize fitness by optimizing energy acquisition through the selection of favorable foraging habitats, but trade-offs exist between time spent in preferred feeding habitats, energetic costs of travel, and reproductive constraints. For pelagic seabirds, geographic distribution of suitable breeding islands can restrict access to marine prey resources and influence foraging strategies. Laysan (Phoebastria immutabilis) and black-footed albatrosses (P. nigripes) breeding in the Northwest Hawaiian Islands, and Indian yellow-nosed albatrosses (Thalassarche carteri) breeding in the Southern Indian Ocean, utilize productive subtropical-subpolar transition zones during their breeding and non-breeding periods, but this marine feature is at a comparatively greater distance for Hawaiian albatrosses during the breeding period due to location of nesting islands. We investigated the foraging behavior and energetics of these three species to evaluate how proximity to preferred marine habitats has influenced their overall foraging strategies. During incubation, all three species traveled to subtropical-subpolar transition zones, however, Hawaiian albatrosses ranged farther to reach this habitat. All species reduced time at sea during brooding, and Hawaiian albatrosses reduced their foraging ranges to distances similar to yellow-nosed albatrosses. As a consequence, Hawaiian albatrosses foraged in the warm, oligotrophic environment of the subtropical gyre during brooding while yellow-nosed albatrosses continued to forage in a subtropical-subpolar transition zone. Landing rates, an indicator of foraging effort, did not differ between reproductive stages and were highly variable within and among species. Hawaiian albatrosses generally spent more time in flight compared to yellow-nosed albatrosses, a strategy that may relate to searching for dispersed and unpredictable prey. Mean absolute field-metabolic rate (FMR) was greatest for black-footed albatrosses, and similar between Laysan and yellow-nosed albatrosses, but mass-specific FMR did not differ between species. Hawaiian albatrosses had lower total body water than yellow-nosed albatrosses (indicating greater lipid reserves), and had FMRs that fell below the allometric relationship for studied albatross species, attributes that likely reflect physiological adaptations for foraging in a low-productivity environment.